2007
DOI: 10.1007/s00167-007-0430-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of medial meniscectomy on gait parameters

Abstract: The aim of this study is to determine how selected gait parameters may change as a result of medial meniscectomy at constant gait speed. Gait analysis using a ZEBRIS ultrasound based three-dimensional motion analysis system was performed in 24 patients who had undergone medial meniscectomy 18 months before the gait analysis. The constant gait speed was 3.5 km/h. Muscle activity was measured by the surface EMG system connected to the system. The muscle groups involved in the tests included (1) m. vastus mediali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 17 publications
2
20
0
3
Order By: Relevance
“…37 Abnormal gait kinematics and kinetics are common after knee injuries such as ACL reconstruction [38][39][40] and meniscectomy. 41 Altered gait patterns after knee joint reconstruction may persist for 8 39 to 12 42 months and for years after major joint trauma and reconstruc- 17 2001 (ACLr) Urbach and Awiszus, 22 2002 (ACLd) Williams et al, 21 2002 ( tion. 43 Evidence also exists of altered lower extremity kinetics during a seated leg press 44 and during gait 32,45 after an artificial knee joint effusion.…”
Section: Discussionmentioning
confidence: 99%
“…37 Abnormal gait kinematics and kinetics are common after knee injuries such as ACL reconstruction [38][39][40] and meniscectomy. 41 Altered gait patterns after knee joint reconstruction may persist for 8 39 to 12 42 months and for years after major joint trauma and reconstruc- 17 2001 (ACLr) Urbach and Awiszus, 22 2002 (ACLd) Williams et al, 21 2002 ( tion. 43 Evidence also exists of altered lower extremity kinetics during a seated leg press 44 and during gait 32,45 after an artificial knee joint effusion.…”
Section: Discussionmentioning
confidence: 99%
“…42 Despite the minimally invasive nature, studies have shown that patients undergoing arthroscopic meniscectomy have pain, effusion, loss of range of motion (ROM), functional changes, neuromuscular and biomechanical changes, loss of quadriceps muscle strength, and a reduced quality of life. 5,8,12,13,27,30,31,33 Herrlin et al 17 showed that for middleaged patients with simple lesions in the meniscus, physical therapy has yielded T T STUDY DESIGN: Systematic review with metaanalysis.…”
mentioning
confidence: 99%
“…The average of individuals' spatial and temporal parameters (Table 2) are not analysed here as they have already been published in detail [8,17,21]. In summary, we can establish that the spatial and temporal parameters depend on age, sports, and the different orthopaedical diseases.…”
Section: Resultsmentioning
confidence: 98%
“…Since ultrasound-based measuring and recording techniques were developed, gait analysis has been frequently used in almost all fields of human locomotion [18]. An ultrasound-based measuring system is used for functional performance assessment after treatment or surgery such as anterior ligament reconstruction surgery [20], meniscectomy [21], hip [17] and knee arthoplasty [7]. The system is useful for analysing the effects of osteoarthrithis [8] and sports [19].…”
Section: Introductionmentioning
confidence: 99%